Edukasi Menyusui terhadap Peningkatan Efikasi Diri dalam Menyusui - Herlena, Herlena; Tanberika, Fajar Sari; Mardiya, Rizka; Yanti, Rifa (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of breastfeeding education on improving breastfeeding self-efficacy among breastfeeding mothers at the Pangkalan Kasai Community Health Center (UPT Puskesmas) in Indragiri Hulu Regency. The method used was a quantitative study with a pre-experimental design using a one-group pretest-posttest. The results, using the Wilcoxon signed-rank test, yielded a p-value of 0.025 (p < 0.05). In conclusion, breastfeeding education significantly improves maternal breastfeeding self-efficacy and should be implemented as a routine education program in healthcare facilities. Keywords: Breastfeeding Education, Self-Efficacy, Breastfeeding